Putting theory to work : how are theories actually used in practice? - Canestri, Jorge, ....- (London : Karnac., 2012)
This book contains a continuation and expansion of the topics covered in the author's previous book, Psychoanalysis: from Practice to Theory, about the use of theories in analytic practice. As a member of the International Psychoanalytical Association (IPA) Conceptual Research Committee and Chair of the Working Party on Theoretical Issues, the author, who teaches at Nanterre University, has studied and taught on the subject for several years, as well as writing many articles on it. The book will be particularly useful for psychoanalytical and psychotherapeutic societies, as well as for research committees.
Keywords: Psychoanalyse